An Analysis of Lead Content in the Tamarindus indica and Samanea saman Leaves in Garum District, Blitar - Sely Tunjung Manik; Elly Purwanti; Wahyu Prihanta (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The increasing number of motorcycle will increase the air polution. For about 2900 motorcycles have increased in Blitar. Such the negative impact of the lead (Pb) was put out by vehicle’s gas emission toward human health, it needs an action to reduce Pb from the air, by utilizing the plants which can absorb Pb. The purposes of this research are to analyze the differences of the Pb contents on the Samanea saman and Tamarindus indica leaves at the street of Pojok, Sumberdiren, Bence, and Slorok and make the correlations between traffic jam and the number of stomata due to the content of Pb.This research was located in Garum Blitar on May 2015. The researcher measured the lead content in sample by using AAS (Atomic Absorption Spectrophotometry) through camouflage method. The calculation of the traffic jam used the handtaly couter. Mean while the number of stomata’s calculation was done directly by using a microscope binokuler Olympus CX21LED.The result showed that the content of Pb in Samanea saman leaves in Pojok, Sumberdiren, Bence, and Slorok were 3,24-0,76 ppm and the lead content on the Tamarindus indica leaves were 0,73-0,69 ppm. In conclusion the researcher find that much more lead were found in Samanea saman leaves. Based on the correlation test there is strong correlation in the number of pb with traffic jam and the number of stomata.Keywords:  motorcycles, lead (Pb), Samanea saman, Tamarindus indica, traffic jam